Weaving through the maze of terrorist marriages in Africa’s Sahel region: Jama’at Nasr al-Islam wal Muslimin (JNIM) under review - Frederick Appiah Afriyie (Cogent Social Sciences, 2024)
The creation of Jama’at Nasr al-Islam wal Muslimin(JNIM), a lethal extremist organization, from the merger of many terrorist organizations, including the Saharan branch of Al-Qaeda in the Islamic Maghreb (AQIM), Al-Mourabitoun, Macina Liberation Front (MLF), and Ansar Dine .The Sahel is overwhelmed by the wave of attacks that the group has launched since their merger in 2017, which has resulted in nearly 8,000 fatalities, the displacement of millions of civilians, attacks on government officials and traditional leaders, the closure of thousands of schools, and severely stunted economic growth. Since 2017, Jama’at Nasr al-Islam wal Muslimin (JNIM) has been blamed for more than 64% of all violent occurrences in the Sahel area, which includes northern Mali and southeast Burkina Faso. The paper’s stated objective is to look into the underlying causes of JNIM’s excessive radicalism in the Sahel.